Att tydliggöra mobbningssignalerna för skolan - Nori, Nadia (2014)
This study is a qualitative study whose aim is to expose bullying tones for school, so as to be able to tackle bullying at an earlier stage. Through this study, those who attend the school have a deeper understanding of bullying. These questions have been around how bullying takes the form, what students and teachers think about bullying, the bullying happens, what a bully and bullies are victims. For the interviews, a semi-structured interview guide with openness to supplementary questions. There were two focus group interviews with students in high school in Luleå vocational program, grades 2 and 3. To capture teachers' perspectives on bullying so interviewed two pieces individually. The interviews were collected, transcribed and then analyzed. The Interviews is the empirical basis for the study. To strengthen the study's reliability was used theory concepts from the authors Asa Wettergren , Gunnar Höistad , Dan Olweus and Klaus Helkama . The results of the study revealed that bullying is when a person or persons, on several occasions, and for a certain time, say or do offensive and unpleasant things against someone who is defenseless. Bullying can be performed in different ways such as by physical contact that is, when a person pushes, turns, pinching, or any kicks. One can also perform psychological bullying that is, in words, grimaces or intentional exclusion from the circle of friends. The study has also shown that bullying has taken broader forms where there is more on the line today when the electronics have increased and those children and young people have easier access to the network. It also is important to mention is that bullying is different between boys and girls and that childhood relationship plays a role if you get aggressive children or not. Validerat; 20140703 (global_studentproject_submitter)